Sosialisasi Hukum Islam Tentang Larangan Perkawinan Adat Jilu oleh Para Tokoh Agama di Desa Tulung Madiun - Sa'diyah, Chalimatus; Kusumawati, Ita Rahmania (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The existence of a prohibition on marriage customs which is still strongly perpetuated in society with the belief that those who violate it will suffer bad luck, resulting in various differences of opinion among the local community, especially the younger generation regarding the applicable laws and regulations. Until now, the jilu custom is still developing into the social culture of society and has become a very strong doctrine of thought.Purposes of Devotion: The aim of this service is to provide a legal understanding regarding the issue of the prohibition of traditional jilu marriages from the perspective of Islamic law in the 'Urf theory.Method of Devotion: Carried out using research methods in the form of empirical methods, namely in the form of observations, interviews related to problems that will be presented in the form of socialization and legal counseling by inviting several religious figures and village officials who will be resource persons, presenter.Results of the Devotion: The result of this service is that it is important for the community to understand Islamic law regarding customs and marriage, so that traditional prohibitions can still be used as a reference and do not conflict with Islamic law. Of course, this aims to filter the problem of ancestral beliefs with the legal provisions that apply in Islam.